Making the knowledge worker as a lifestyle learner - Phoewhawm R. (2014)
This study describes how knowledge was applied in the ancient periods so that practitioners of knowledge management can truly see and appreciate how knowledge is genuine in itself. The research objective is to have the managerial team become a self-managed team that utilises their knowledge for contributing to the organisation/company's goal and team performance. The metaphor of North American football is utilised as a philosophical and conceptual learning tool for building employees' analytical thinking skills to support team performance. The study provides an application script for management to articulate the methodological ideas of the sports into the business core operation. Copyright © 2011 Inderscience Enterprises Ltd.